Arthur Napoleão, the Virtuous Piano and the Chessboard: an Exercise in Sociability from the Empire to the Republic - Medeiros, Alexandre Raicevich de (Revista do Instituto Histórico e Geográfico Brasileiro, 2024)
The article discusses the importance of Arthur Napoleão (1843-1925), a composer and pianist from Porto who contributed to the development of a network of cultural sociability in Rio de Janeiro at the end of the 19th century. As an entrepreneur and cultural mediator, he introduced his music into the socio-cultural environment of Rio de Janeiro after settling definitively in Brazil in 1868, where he consolidated his work as a musician. Throughout his life, he helped set up commercial establishments focused on the sale of pianos and musical scores, which became important spaces of sociability in the Court and, later, in the capital of the Republic. Parallel to his musical activities, he was also a keen chess player who helped to develop and promote the game in the city of Rio de Janeiro.